Silencing SOCS1 via Liposome-Packed siRNA Sustains TLR4-Ligand Adjuvant - Hildebrand, Dagmar; Metz-Zumaran, Camila; Jaschkowitz, Greta; Heeg, Klaus (Frontiers in Immunology, 2019)
Infectious diseases remain one of the leading causes of death worldwide. Vaccination is a powerful instrument to avert a variety of those by inducing a pathogen-specific immune response and ensure a long-lasting protection against the respective infection. Nevertheless, due to increasing numbers of immunocompromised patients and emergence of more aggressive pathogens existing vaccination techniques are limited. In our study we investigated a new strategy to strengthen vaccine adjuvant in order to increase immunity against infectious diseases. The strategy is based on an amplification of Toll like receptor 4 (TLR4) -induced activation of antigen-presenting cells (APCs) by turning off a powerful endogenous inhibitor of APC-activation. TLR4 signaling induces the release of cytokines that bind autocrine and paracrine to receptors, activating the Janus kinase (JAK) 2/ signal transducers and activators of transcription (STAT) 3 cascade. Subsequently, STAT3 induces expression of suppressor of cytokine signaling (SOCS) 1 that terminates the inflammatory response. In the approach, TLR4-adjuvant monophosphoryl lipid A (MPLA)-stimulated monocyte-activation is reinforced and sustained by silencing SOCS1 via lipid nanoparticle-enclosed siRNA (L-siRNA). L-siRNA is transported into primary cells without any toxic side effects and protected from early degradation. Through lipid core-embedded functional groups the lipid particle escapes from endosomes and releases the siRNA when translocated into the cytoplasm. SOCS1is potently silenced, and SOCS1-mediated termination of NFκB signaling is abrogated. Consequently, the MPLA -stimulated activation of APCs, monitored by release of pro-inflammatory cytokines such as IL-6, TNFα and IL-1β, upregulation of MHC class II molecules and costimulatory CD80/CD86 is strongly enhanced and prolonged. SOCS1-silenced APCs, pulsed with liposomal tetanus light chain toxin (TeTxLC) antigen, activate autologous T cells much more intensive than SOCS1-expressing cells. Importantly, expansion of cocultured CD4+ as well as CD8+ T cells is remarkably enhanced. Furthermore, our results point towards a broad T helper cell response as TH1 typical as well as TH2 characteristic cytokines are elevated. Taken together, this study in the human system comprises a translational potential to develop more effective vaccines against infectious diseases by inhibition of the endogenous negative-feedback loop in APCs.